Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Figure T is the result of a transformation on Figure S. Which transformation would accomplish this? 6 -4 -3 2 3 Figure S Figure T -3 -4 -5

Sagot :

Let:

[tex]\begin{gathered} A=(1,-1) \\ A^{\prime}=(3,-2) \\ A\to(x+a,y+b)\to A^{\prime} \\ so\colon \\ 1+a=3 \\ a=3-1=2 \\ ---- \\ -1+b=-2 \\ b=-2+1=-1 \\ so\colon \\ A\to(x+2,y-1)\to A^{\prime} \end{gathered}[/tex]

Therefore, the transformation T is:

A translation 2 units right and 1 unit down